Democracy - Nardo, Don, 1947- (San Diego, CA : Lucent Books, 1994)
Discusses the concept of democracy as it has developed in America and abroad.
Includes bibliographical references (p. 121-123) and index.
Keywords: Democracy -- Juvenile literature; Democracy -- United States -- Juvenile literature; Democracy